Several Characteristics Of The Special International Court For Kosovo - Azem Hajdari (European Scientific Journal, ESJ, 2016)
The Special International Court for Kosovo (hereinafter the Special Court) has been established for adjudication of cross-border and international crimes alleged to have been committed in Kosovo during the period of time January 1, 1998-December 31, 2000. This court consists of Specialized Chambers and the Office of Specialized Prosecutor and they shall be able to conduct investigations, criminal prosecutions and trials of persons alleged to have committed war crimes and crimes against humanity. The Special Court shall perform its activities in Kosovo and in The Kingdom of Netherlands. This court has in its focus the adjudication of crimes included in the Report of the Parliamentary Assembly of the Council of Europe DOK 12462 dated January 7, 2011, crimes reported by Swiss Senator Dick Marty. The Special Court is expected to solve the sustainability of charges on organ trafficking and other serious crimes committed by influential individuals within former KLA, charges which shall be considered a great obstacle in developing and integrating Kosovo processes. In this short scientific paper shall be discussed about the meaning of The Special Court, its jurisdiction, punishments, their execution, the cooperation of this court with national and international institutions etc.